Patients' experiences of recovery: Beyond the intensive care unit and into the community. (21st December 2020) - Calkins, Kelly; Kako, Peninnah; Guttormson, Jill
Abstract: Aims: To understand barriers and facilitators of recovery for critical illness survivors', who are discharged home from the hospital and do not have access to dedicated outpatient care. Design: Multi‐site descriptive study guided by interpretive phenomenology using semi‐structured interviews. Methods: Interviews were conducted between December 2017 ‐July 2018. Eighteen participants were included. Data were collected from interview recordings, transcripts, field notes, and a retrospective chart review for sample demographics. Analysis was completed using Interpretive Phenomenological Analysis which provided a unique view of recovery through the survivors' personal experiences and perception of those experiences. Results: Participants encountered several barriers to their recovery; however, they were resilient and initiated ways to overcome these barriers and assist with their recovery. Facilitators of recovery experienced by survivors included seeking support from family and friends, lifestyle adaptations, and creative management of their multiple medical needs. Barriers included unmet needs experienced by survivors such as mental health issues, coordination of care, and spiritual needs. These unmet needs left participants feeling unsupported from healthcare providers during their recovery. Conclusion: This study highlights important barriers and facilitators experienced by critical illness survivors during recovery that need be addressed by healthcare providers. New ways to support critical illness survivors, that can reach a broader population, must be developed and evaluated to support survivors during their recovery in the community. Impact: This study addressed ICU survivors' barriers and facilitators to recovery. Participants encountered several barriers to recovery at home, such as physical, cognitive, psychosocial, financial, and transportation barriers, however, these survivors were also resilient and resourceful in the development of strategies to try to manage their recovery at home. These results will help healthcare providers develop interventions to better support ICU survivors in the community. 摘要: 目的: 了解出院后回家且无法获得专业门诊护理的危重病幸存者的康复障碍和促进因素。 设计: 在解释性现象学的指导下, 利用半结构式访谈进行多地点描述性研究。 方法: 在2017年12月至2018年7月期间进行访谈。访谈有18名参与者。通过访谈记录、访谈笔录、现场笔记和样本人口统计的回顾性图表审查进行数据采集。采用解释性现象学分析法完成分析, 解释性现象学分析通过幸存者的个人经历和对这些经历的看法, 提供了一个独特的康复观点。 结果: 参与者在康复过程中遇到了一些障碍; 不过, 他们表现出坚韧乐观的态度, 并主动提出了克服这些障碍和帮助康复的方法。幸存者所经历的促进康复的因素包括寻求家人和朋友的支持、调整生活方式以及创造性地管理其多种医疗需求。障碍包括幸存者所经历的未被满足的需求, 如心理健康问题、护理协调和精神需求。这些未被满足的需求使参与者觉得在康复过程中得不到医疗服务提供者的支持。 结论: 本研究强调了危重病幸存者在康复过程中遇到的重要障碍和促进因素, 这些障碍和促进因素需要由医疗服务提供者解决。必须制定和评估支持危重病幸存者的新方法, 以覆盖更广泛的人群, 为幸存者在社区康复期间提供支持。 影响: 本研究涉及ICU幸存者的康复障碍和促进因素。参与者在家休养康复时遇到了一些障碍, 如身体、认知、社会心理、经济和交通障碍, 不过, 在制定居家自身康复管理策略时, 这些幸存者保持着坚韧乐观和理智的态度。这些结果将帮助医疗服务提供者制定干预措施, 以更好地支持社区中的ICU幸存者。